Antihyperglycemic and Antihyperlipidemic Effects of Aqueous Extracts of Lannea edulis in Alloxan-Induced Diabetic Rats - Banda, Michelo; Nyirenda, James; Muzandu, Kaampwe; Sijumbila, Gibson; Mudenda, Steward (Frontiers in Pharmacology, 2018)
Lannea edulis (Sond.) Engl. commonly known as wild grape is used traditionally for the treatment of diabetes. It is only found in Eastern and Southern Africa. Phytochemical screening, antihyperglycemic and antihyperlipidemic effects of aqueous extracts of L. edulis in alloxan induced diabetic rats were carried out. We report herein the findings of this research work. Lannea edulis crude aqueous extracts were obtained by hot infusion and evaporation method. Phytochemical screening was carried out and subsequently toxicity studies of the aqueous extracts were performed to establish the Lethal Dose 50 (LD50) in albino rats. Alloxan monohydrate was used to induce diabetes in the rats. Lannea edulis positive control group doses of 100, 300, and 500 mg/kg were administered to 3 groups for 14 days. The positive control group was administered 5 mg/kg of glibenclamide. The negative and normal control groups were administered distilled water. To determine fasting blood glucose, blood was drawn on days 0, 1, 3, 5, 7, and 14 while it was drawn on days 0 and 14 for the determination of lipids. Phytochemical screening revealed the presence of flavonoids, saponins, tannins, cardiac glycosides, alkaloids and steroids. L. edulis diabetic positive control groups showed significant (P < 0.05) dose dependent reductions in fasting blood glucose levels. When day 0 mean blood glucose levels were compared to day 3 mean blood glucose levels of their respective groups, the 300 mg/kg L. edulis group showed a 23.3% drop and the 500 mg/kg L. edulis group showed a 52.6% drop. The 100 mg/kg L. edulis diabetic positive control group showed a 25.1% drop by day 5, the day on which it showed statistical significance (P < 0.05) compared to the diabetic control. In addition, administration of aqueous extracts of L. edulis to diabetic rats for 14 days significantly decreased (P < 0.05) the levels of serum total cholesterol, triglycerides, Low Density Lipoprotein (LDL) and Very Low Density Lipoprotein (VLDL) whilst increasing the levels of High Density Lipoprotein (HDL), when compared to the diabetic control group. It was concluded that L. edulis showed significant and dose dependent antihyperglycemic and antihyperlipidemic effects thus confirming its traditional use.